(untitled) (مجلة جامعة اللاذقية - سلسلة العلوم الأساسية, 2016)
تمّ إيجاد الصّيغ الموحية لاهتزاز موجة الكثافة لسائل كوانتي مكوّن من فيرميونات ذات سبين كسري في إطار نظرية لانداو ومعاملاته في سائل فيرفي.اعتماداً على المعادلة الحركيّة الناتجة عن معادلة بولتزمان – لانداو لإيجاد سرعة الصّوت في ذلك السائل، وضمن المجال اللاتصادمي [ ]،وتحت تأثير حقل كهرطيسي خارجي. تمّ مقارنة نتائجنا مع ما توصل إليه عدد من الباحثين لحساب تلك السرعة بتابعية ( )،وذلك لبيان مدى تأثير ذلك الحقل على سرعة اهتزاز موجة الصّوت في الأوساط الحقيقية. We found the vibration wave density formula of quantum liquid formed of quasi- particles fermionic system in Landaau parameters ( ) frame. This depends on the kinetic equation produced from Boltzmann – Landau equation, to find the sound – wave through that liquid and in non- colliding field ( ) and under external electromagnetic field. We compared our results with the previous works for the sound – speed calculation as a function of parameters to find the effect of that field on the sound – wave-vibrational velocity, in the real – media.